More help in fight againt weeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Weeds can destroy up to 45% of crops in developing countries - and can make the difference between life and death for some people. The South East Asian Weed Information Centre (SEAWIC) is now helping the small farmers of that region to combat this...